2010
DOI: 10.1103/physrevlett.104.018101
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Elasticity: Connecting All-Atom Simulations with Continuum Mechanics

Abstract: The mechanical properties of microtubules have been extensively studied using a wide range of biophysical techniques, seeking to understand the mechanics of these cylindrical polymers. Here we develop a method for connecting all-atom molecular dynamics simulations with continuum mechanics and show how this can be applied to understand microtubule mechanics. Our coarse-graining technique applied to the microscopic simulation system yields consistent predictions for the Young's modulus and persistence length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 25 publications
9
76
0
Order By: Relevance
“…Interestingly, it has been reported that microtubules have a length-or wavelength-dependent stiffness (Pampaloni et al, 2006;Taute et al, 2008), and the elastic anisotropy of their structure has been implicated as the cause of this (Heussinger et al, 2010). However, it was also noted that the degree of anisotropic elasticity required to account for the reported length dependence is extremely large, and much larger than recent detailed simulations found (Sept and MacKintosh, 2010). Moreover, AFM experiments probing the response of microtubules to radial forces have not shown evidence for significant anisotropy (de Pablo et al, 2003).…”
Section: Wormlike Bundlesmentioning
confidence: 99%
“…Interestingly, it has been reported that microtubules have a length-or wavelength-dependent stiffness (Pampaloni et al, 2006;Taute et al, 2008), and the elastic anisotropy of their structure has been implicated as the cause of this (Heussinger et al, 2010). However, it was also noted that the degree of anisotropic elasticity required to account for the reported length dependence is extremely large, and much larger than recent detailed simulations found (Sept and MacKintosh, 2010). Moreover, AFM experiments probing the response of microtubules to radial forces have not shown evidence for significant anisotropy (de Pablo et al, 2003).…”
Section: Wormlike Bundlesmentioning
confidence: 99%
“…The much larger values of κ that have been obtained in [25,27] as discussed above would lead to a ratio k/κ close to the lower bound (10).…”
Section: Model Parameters For Mechanically Stable Tubular Structuresmentioning
confidence: 77%
“…The other estimates κ ∼ 3000k B T from [25] and κ ∼ 300k B T from [27], however, violate this constraint. If κ-values violating the upper bound (14) are confirmed experimentally in the future, this can be a hint that the allosteric model itself, i.e., the assumption that GTP hydrolysis changes the tubulin dimer angle, is inconsistent.…”
Section: Hydrolysis and Mechanical Model Parametersmentioning
confidence: 83%
See 1 more Smart Citation
“…For microtubules (one of the main load-bearing structures in cells), K s has been reported to lie anywhere from 1 MPa to 10 GPa, with values being strongly dependent on experimental conditions and interpretation of data (Kasas et al 2004). Recent atomistic simulations place the K s of microtubules between 100 MPa and 1 GPa, depending on the specific structure (Sept and MacKintosh 2010). Similarly, organelles display vastly different compressibility.…”
Section: Mathematical Modelingmentioning
confidence: 99%